2023
DOI: 10.1186/s13046-023-02667-4
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput and targeted drug screens identify pharmacological candidates against MiT-translocation renal cell carcinoma

Abstract: Background MiT-Renal Cell Carcinoma (RCC) is characterized by genomic translocations involving microphthalmia-associated transcription factor (MiT) family members TFE3, TFEB, or MITF. MiT-RCC represents a specific subtype of sporadic RCC that is predominantly seen in young patients and can present with heterogeneous histological features making diagnosis challenging. Moreover, the disease biology of this aggressive cancer is poorly understood and there is no accepted standard of care therapy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…We analyzed the mRNA expression of some known TFEB-target genes in TFEB dTAG/dTAG U2OS cells stably expressing HA-bromoTAG, HA-bromoTAG-PPP2CA or HA-bromoTAG-PPP2CA H118Q by RT-qPCR following 8 h of BDPIC treatment. We observed that compared to DMSO control, BDPIC treatment induced only a slight but significant increase in expression of Fnip 1 , Flcn , 21 , 43 and Gpnmb 47 , 48 , 49 transcripts in cells expressing HA-bromoTAG-PPP2CA but not in those expressing HA-bromoTAG or HA-bromoTAG-PPP2CA H118Q ( Figure 4 C), suggesting that targeted dephosphorylation of TFEB-dTAG by BDPIC is potentially sufficient to cause transcriptional activation of TFEB. The transcription of Hexa , another TFEB-target gene, was not significantly affected by targeted dephosphorylation of TFEB-dTAG by BDPIC ( Figure 4 C).…”
Section: Resultsmentioning
confidence: 95%
“…We analyzed the mRNA expression of some known TFEB-target genes in TFEB dTAG/dTAG U2OS cells stably expressing HA-bromoTAG, HA-bromoTAG-PPP2CA or HA-bromoTAG-PPP2CA H118Q by RT-qPCR following 8 h of BDPIC treatment. We observed that compared to DMSO control, BDPIC treatment induced only a slight but significant increase in expression of Fnip 1 , Flcn , 21 , 43 and Gpnmb 47 , 48 , 49 transcripts in cells expressing HA-bromoTAG-PPP2CA but not in those expressing HA-bromoTAG or HA-bromoTAG-PPP2CA H118Q ( Figure 4 C), suggesting that targeted dephosphorylation of TFEB-dTAG by BDPIC is potentially sufficient to cause transcriptional activation of TFEB. The transcription of Hexa , another TFEB-target gene, was not significantly affected by targeted dephosphorylation of TFEB-dTAG by BDPIC ( Figure 4 C).…”
Section: Resultsmentioning
confidence: 95%
“…Mutations and/or aberrant expression of MiTF/TFE family members have been associated with different types of cancers in humans, such as renal carcinomas, alveolar sarcomas, and melanomas ( 4 ). MiTF/TFE family factors are also involved in the regulation of lysosomal signaling, including mTOR complex 1 (mTORC1) and the Wnt/β-catenin pathway, which are critical for oncogenic signaling ( 5 , 6 ). Most metastatic RCCs are treated with tyrosine kinase inhibitors (TKIs) targeting vascular endothelial growth factor receptor (VEGFR), including pazopanib, sunitinib, sorafenib, bevacizumab, ramucirumab, and cabozantinib ( 1 , 7 - 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction in TFEB and TFE3 signaling has been observed in neurodegenerative diseases, lysosomal storage disorders, and various types of cancer [ 15 , 20 ]; consistent with this concept, strategies targeting TFEB and TFE3 have shown promise in promoting cellular clearance in cellular and animal models of diseases characterized by the accumulation of metabolic intermediate products or protein aggregates [ 21 ], including lysosomal storage diseases [ 21 , 22 ], Parkinson [ 23–25 ], Alzheimer [ 26–28 ], Huntington diseases [ 29 ], SERPINA1/α1-anti-trypsin deficiency [ 30 ], spinal bulbar muscular atrophy [ 31 ] and diet-induced obesity [ 11 ]. While, several lines of evidence suggest that the identification of clinically compatible MiT/TFE inhibitors may offer a rational therapeutic avenue for the treatment of pathologies induced by TFEB, TFE3 and MITF overexpression or hyperactivation, such as MiT-renal cell carcinoma [ 32 ], Birt-Hogg-Dubé syndrome [ 33 ], tuberous sclerosis [ 34 , 35 ] and malignant melanoma [ 36 ]. Despite the large body of preclinical data suggesting a therapeutic potential of modulating MiT/TFE member, there are currently no clinical applications.…”
Section: Introductionmentioning
confidence: 99%